2019
DOI: 10.1049/el.2018.8035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of epitaxial layer's thickness on spectral response of 4H‐SiC p‐i‐n ultraviolet photodiodes

Abstract: 4H-SiC ultraviolet p-in photodiodes with four different epitaxial structures were fabricated. The experimental results prove that both a thin P +-type Ohmic contact layer and a thick intrinsic layer were indispensible for a high-performance ultraviolet p-in photodiode. A 4H-SiC p-in photodiode with responsivity as high as 0.139 A/W at 278 nm incident wavelength was achieved. Meanwhile, within a certain wavelength range, the peak response wavelength of an ultraviolet p-in photodiode would be modulated by proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
1
3
0
1
Order By: Relevance
“…It should be noted that the values of the maximum sensitivity and the corresponding wavelengths practically coincide with the results of calculations in [9,10]. Attention is drawn to the fact that even at d = 0.45 microns in the absence of anti-reflective coatings at a wavelength of 295 nm, the maximum values of sensitivity and EQY are equal to 0.156 A/W and 0.64 electrons/ photons, respectively, which is not inferior to known analogues.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…It should be noted that the values of the maximum sensitivity and the corresponding wavelengths practically coincide with the results of calculations in [9,10]. Attention is drawn to the fact that even at d = 0.45 microns in the absence of anti-reflective coatings at a wavelength of 295 nm, the maximum values of sensitivity and EQY are equal to 0.156 A/W and 0.64 electrons/ photons, respectively, which is not inferior to known analogues.…”
Section: Resultssupporting
confidence: 76%
“…It is known that one of the most important areas of research and development is the search for optimal design options for the PDs, which would provide an optimal combination of low dark currents, high photosensitivity (quantum yield) and [8] performance. Ensuring high sensitivity (especially in the short-wave UV-region) will be determined by the properties of the external photodetector layer (usually p + ) and, first of all, its thickness [9], which should be minimal, as well as the presence or absence of no anti-reflective coating [10]. The results of our preliminary studies showed that 4H-SiC photodiodes made on the basis of epitaxial structures with ultrathin (< 0.1 microns) external p + -layers were characterized by large (> 10 −8 A) by reverse currents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Известно, что одним из важнейших направлений исследований и разработок является поиск оптимальных вариантов конструкции ФП, который обеспечивал бы оптимальное сочетание малых темновых токов, высокой фоточувствительности (квантового выхода) и быстродействия [8]. Обеспечение высокой чувствительности (особенно в коротковолновой УФ--области) будет определяться свойствами внешнего фотоприемного слоя (обычно p + ) и в первую очередь его толщиной [9], которая должна быть минимальна, а также наличием или отсутствием на нем антиотражающего покрытия [10]. Результаты наших предварительных исследований показали, что 4H-SiC-фотодиоды, выпол-ненные на основе эпитаксиальных структур с ультратонкими (< 0.1 мкм) внешними p + -слоями, характеризовались большими (> 10 −8 A) обратными токами.…”
Section: Introductionunclassified
“…Various structure types of 4H-SiC UV PDs have been studied, including Schottky PD [10,11], metal-semiconductor-metal PD [12,13], traditional p-i-n PD [14], traditional separated-absorption-multiplication (SAM) avalanche photodiode (APD) [15], and junction field-effect transistor [16]. The traditional 4H-SiC p-i-n PD has the merits of low operation voltage, high and bias-independent photoresponse, low-noise and high response speed [17,18]. However, to achieve the above merits, an intrinsic layer (i layer) with low doping concentration and relatively large thickness (>1.5μm) should be employed as an absorption region, which will result in ultrahigh avalanche breakdown voltage and limit the application in UV weak signal and single photon detection [19].…”
mentioning
confidence: 99%